Legal terminology at arm's length - Kocbek, Alenka (Linguistica (Ljubljana), 2013)
The paper is aimed at shedding new light on the multiple dimensions of legal terms which can be unearthed in the process of terminology mining as a crucial stage in translation. It proposes to view legal terminology from a sociocognitive perspective, according to which terms are perceived as expressing units of understanding based oncognitive frames rather than rendering concepts in their traditional definition. Upon closer scrutiny most of these units reveal significant information regarding their verbal and extra-verbal dimensions. We therefore suggest analysing units of understanding expressed by simple terms, multiple elements terms and phraseology as depositories of knowledge providing information on the text type in which they occur, as well as on there levant area of law, the legal system and the wider culture underlying the text. In this context, terminology mining is not intended merely as extraction of terms, but rather as their analysis, comparison and structuring which reveals aspects such as their multiple embeddedness, as well as their historical, ideological, metaphorical, status-conferringand common Latin dimension.
Keywords: approche socio-cognitive; prevajanje; sociokognitivni pristop; terminologie juridique; terminologija; terminology; traduction; translation